Respuesta :
The equivalent expressions are:
[tex]7(-\frac{3}{4}x - 3) = (7 \times \frac{-3}{4}x) + (7 \times -3)\\\\7(-\frac{3}{4}x - 3) = \frac{-21x}{4} - 21[/tex]
Solution:
Given expression is:
[tex]7(-\frac{3}{4}x - 3)[/tex]
We have to find the equivalent expressions
By distributive property,
a(b + c) = ab + ac
Therefore,
[tex]7(-\frac{3}{4}x - 3) = (7 \times \frac{-3}{4}x) + (7 \times -3)\\\\7(-\frac{3}{4}x - 3) = \frac{-21x}{4} - 21[/tex]
Thus equivalent expressions are found
Answer:
Im pretty sure its a and e
Step-by-step explanation:
lmk if im wrong or right